MANAJEMEN PEMBAHARUAN PENDIDIKAN ANAK USIA DINI DI PAUD LUTHFILLAH KOTA PALANGKA RAYA - Noor Aisyah (Al-Manba, 2026)
The most recent research conducted by experts on early childhood development shows that children are ready to learn and respond to everything in their environment from an early age, even while still in their mother's womb. This theory also refutes the old theory that recommended that education should only begin when a child is 7 years old. Thus, this new theory has shifted the paradigm of early childhood education management, which goes beyond simply providing games or learning through play, but also requires the ability to design effective learning programs, starting from planning, implementation, and assessment. Therefore, it is necessary to renew the management of early childhood education so that it can run effectively, efficiently, productively, and accountably. The management of early childhood education renewal at PAUD Luthfillah has been implemented and some have not been implemented, starting from planning, implementation to assessment, although the changes/renewals have been planned, in practice they have not been implemented due to several inhibiting factors, such as renewal in terms of planning, the inhibiting factor is the teacher himself who is not competent in making RKH, in terms of learning renewal, the inhibiting factor is inadequate facilities and unavailable learning resources, in terms of activity patterns, the inhibiting factor is the teacher who is also not active in implementing learning activity patterns according to the age characteristics of students in childcare (TPA) and in terms of assessment, the report card system has its own advantages and disadvantages.